Perceived human resource system strength and employee reactions toward change: Revisiting human resource's remit as change agent. Issue 3 (24th January 2019) - Alfes, Kerstin; Shantz, Amanda D.; Bailey, Catherine; Conway, Edel; Monks, Kathy; Fu, Na
Abstract : Although scholars have highlighted human resource's (HR's) important role as a change agent, we know little about the extent to which HR influences the change context to foster positive employee responses and support organizational changes. This study positions perceived HR system strength as an important internal context factor that influences employees' reactions toward change. Drawing on emotion theory and social exchange theory, we analyze the mechanisms through which employees' perceptions of HR system strength lead to positive employee responses to organizational change. Data from 704 employees in a UK police force showed that employees' perceptions of HR system strength were positively related to their ability to cope with organizational change and that this relationship was simultaneously mediated by state positive affect and perceived organizational support. Moreover, our findings demonstrated that coping with organizational change was positively related to employees' change‐supportive behavior. This study is important because it broadens the remit of HR's role as change agent and provides valuable insight into how HR positively influences employee outcomes during organizational change.